1990
DOI: 10.1080/00405009008658323
|View full text |Cite
|
Sign up to set email alerts
|

The Handle of Double-jersey Knitted Fabrics Part I: Polar Profiles

Abstract: The principal properties involved in evaluating handle subjectively are identified and quantitatively described. In addition, these properties are linked to known methods of measuring tbe various physical properties involved.A study of a small group of commercially manufactured double-jersey fabrics produced a method of recording results in the form of a polar diagram. This exercise indicated that the resulting profile could discriminate pictorially between fabrics that incorporated variations in fibres, yam s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…Many researchers [ 1,2,3,4,6] have already reported that consumers are consistently able to detect differences ' Each number in the parentheses represents a different sample that varies in terms of cover factor or yarn thickness. Further, the samples will be cited in this paper in the form of C-l, C'-1, and so on.…”
Section: Sensory Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…Many researchers [ 1,2,3,4,6] have already reported that consumers are consistently able to detect differences ' Each number in the parentheses represents a different sample that varies in terms of cover factor or yarn thickness. Further, the samples will be cited in this paper in the form of C-l, C'-1, and so on.…”
Section: Sensory Measurementsmentioning
confidence: 98%
“…To ensure that the judges were using the fixed pressure, they were asked to check it frequently on the weighing machine during the experiment. 3. To detect a difference in the coefficient of friction, again the judges were asked to press the platform of the weighing machine with the index finger up to a maximum pressure of 25 gf/CM2.…”
Section: Paired Comparison and Handling Mannermentioning
confidence: 99%
“…The responses of consumers to fabrics have been known to be influenced by psychological factors such as affective impression, color preference, fashion, culture and their own way of evaluation (Winakor et al 1980;Hallos et al 1990;Kulkarni 1995). However, Hallos et al (1990) found that, in the evaluation of double-jersey knit fabrics, there was a close agreement between the ranking obtained from inexperienced judges who used a combination of sight and touch and the results obtained from an instrumental method for attributes of weight, thickness, fullness, smoothness (friction), extensibility and compressibility (hardness).…”
Section: Introductionmentioning
confidence: 99%
“…Others have reported that the mechanical properties of knitted fabrics vary According to knit structures, fibers, yarns, and densities, which in turn affect the knit's hand significantly [4][5][12][13][14].…”
mentioning
confidence: 98%